Healing grief : reclaiming life after any loss - Van Praagh, James (Hodder Headline, 2000)
Imprint. Best-selling author James Van Praagh charts a course for coping with the death of a parent, a spouse or a child, as well as such life passages as the end of a marriage or the onset of disease.